Analysis of database about vaccination against human papillomavirus in sergipe in 2014 - Azevedo, Dulcilene Santos; Albuquerque, Waleska da Silva; Monteiro, Bruna Karoline Santos Melo; Farias, Thayana Santos de; Santos, Vivian Roberta Lima; Dias, Júlia Maria Gonçalves (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: The development of the Human papillomavirus vaccine has created the possibility of action at the primary level for the prevention of cervical cancer and precancerous lesions. Objective: To analyze the data obtained by the introduction of the vaccine against papillomavirus in the state of Sergipe, quantifying the sampling population of girls met in 2014 and quantify the hit target by each micro-region of the state. Methods: Cross-sectional analysis, descriptive with retrospective component, using only secondary data from the Health State Department - Sergipe, concerning the vaccination coverage of vaccine against human papillomavirus from March 2014 to December 2014 in 11 to 13-year-old girls. Wilcoxon test was used for mean differences in the paired regions, ages and both. Results: In the analysis of the study period, a total population of 11 to 13-year-old girls, 61785 received the first dose of the vaccine (D1), reaching a 103.25% coverage and, 30,561 of these received the second dose of vaccine, resulting in a 56.26% coverage. In all analyzed regions decreasing doses applied between the first (D1) and the second dose (D2) were found. In this analysis, the confidence interval to 95% were all small and all data were analyzed statistically significant at p<0.001. Conclusion: All micro-regions reached the vaccination goal of the State Departament of Health in the application of the first doses and two of them were above the national average. However, none reached the target in the second dose, four micro-regions were below the national average and tree above. The age group of 12 years was the only one to not reach the goal neither in the first nor in the second dose.